2021
DOI: 10.1515/ijfe-2021-0050
|View full text |Cite
|
Sign up to set email alerts
|

Impact of high-intensity ultrasound on the physicochemical and functional properties of a protein isolate from passion fruit (Passiflora edulis) seeds

Abstract: A protein isolate from passion fruit seeds (PFSPI) obtained by alkaline extraction and isoelectric precipitation was treated with sonication for 15 and 30 min at 40 kHz to evaluate its impact on the physicochemical and functional properties. The PFSPI had a purity of 96.21% protein, with albumins being the main fraction (75.66%). Ultrasound increased the bulk density (ρ) of PFSPI by 13.3% and the formation a more porous structure by a greater separation between particles. Protein solubility of PFSPI in the ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 56 publications
4
10
1
Order By: Relevance
“…The reduction in W a iin sonicated protein isolates is due to structural modification of the proteins, which facilitates the removal of a greater amount of free water during freeze-drying [18] . Reductions in W a by effect of ultrasound also have been reported for protein isolates from fruit passion [16] , jackfruit [15] and guamuchil [18] seed fruits. The W a values of SSPI of this study (0.404–0.502) were below of the limit value (0.660) considered as safe to prevent the microbiological decay in foods [56] .…”
Section: Resultsmentioning
confidence: 59%
See 3 more Smart Citations
“…The reduction in W a iin sonicated protein isolates is due to structural modification of the proteins, which facilitates the removal of a greater amount of free water during freeze-drying [18] . Reductions in W a by effect of ultrasound also have been reported for protein isolates from fruit passion [16] , jackfruit [15] and guamuchil [18] seed fruits. The W a values of SSPI of this study (0.404–0.502) were below of the limit value (0.660) considered as safe to prevent the microbiological decay in foods [56] .…”
Section: Resultsmentioning
confidence: 59%
“…The highest augment on the protein content by effect ultrasound was 5.9 %, increasing from 78.3 % (0 W) to 82.9 % (600 W/30 min). On the other hands, reductions of 70.6 % (400 W/30 min) and 69.2 % (600 W/30 min) also were observed for lipids and moisture contents, respectively, with respect to 0 W. The reduction in the moisture content could be due to the structural modification of the proteins because of the ultrasonic cavitation, which promotes easier and greater water removal [16] . The decrease in moisture content by ultrasound could be the cause of a concentrating effect of the protein content in the SSPI [50] .…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Espinosa‐Murillo et al. (2021) found that the treatment with an ultrasonic bath (40 kHz; 300 W for 15 and 30 min) increased the protein solubility and foaming capacity of protein isolate from fruit passion seeds.…”
Section: Ultrasound Technology In Foodmentioning
confidence: 99%